A comment on 'pseudowork'. (6th June 2017) - Cross, Rod
Abstract: When an external force is applied to an extended object, the change in total energy may involve a change in the kinetic energy of the centre of mass, plus a change in the rotational energy and perhaps a change in the stored elastic energy. The work done by the external force is illustrated using two simple examples, showing why some authors prefer to classify the work as either 'pseudowork' or 'real' work.